Bauhinia ungulata L.: Medicinal Utilization, Botanical Aspects, Biological Properties and Chemical Constitution Reported in the Literature - Remígio, Myrth Soares do Nascimento; da Silva, Andressa Santa Brígida; Rossi, Alessandra; Barbosa, Wagner Luiz Ramos (Pharmacognosy Reviews)
Bauhinia ungulata L. (Leguminosae) is a plant species popularly known as “mororó” or “pata-de-vaca”, whose leaves are used in Brazil as infusion, mainly to treat diabetes. Due to its wide utilization and its therapeutic potential, this species has been investigated, producing data that were organized and arranged in this review, in order to provide an overview of different aspects of the species. A search for articles published until December 2021 on medicinal utilization, botanical characterization, bioactivities, and chemical constitution of the species was carried out, consulting the databases PubMed, Scopus, Lilacs, SciELO, Google Scholar, and Capes Journal Portal. The selected articles describe 31 different terpenes, characterized in essential oils from B. ungulata leaves; in addition, other 20 substances, including flavonoids, alkaloids, steroids, and triterpenoids, in other derivatives obtained from leaves, roots, or stems of the species were described. In these articles, different activities were reported, such as antioxidant, anti-inflammatory, antidepressant/anxiolytic, antimicrobial, antiproliferative, larvicidal, cytotoxic and wound healing. The published data on the species allow to infer a potential of use as a therapeutic ingredient with antioxidant activity, which is the most investigated activity and has been related to phenolic compounds, especially flavonoids. Despite the popular use of leaves of the species, as an infusion to treat diabetes, to be well described in the literature, no records were found on the evaluation of their antidiabetic potential or about the characterization of substances present in aqueous extracts from B. ungulata.
Keywords: Bioactivities; Flavonoids; Medicinal Uses; “pata-de-vaca”; Phytochemical Constituents; Terpenes